Non-monetary incentives for middle managers in Malaysia - Wee Yu Ghee (2010)
This study investigates the top five most influential non-monetary work motivators for middle managers in Malaysia. Based on a study of 172 middle managers in the country, the results showed that the five most attractive non-monetary incentives which tend to motivate the middle managers and consequently affect their level of job satisfaction include (1) trust, (2) achievement, (3) relationships between supervisors, peers and subordinates, (4) growth and (5) freedom and autonomy. Having identified these top five non-monetary drivers, top level of management or board of directors can apply this useful information as a reference point, so as to create an environment that promotes and sustains motivation level at the workplace. The needs of managers such as wanting to be trusted, desiring to achieve certain successful tasks and hoping for close relationship with colleagues must be addressed by organizations in Malaysia if they expect middle managers to be satisfied with their jobs. However, just like other studies, this research is subjected to its own limitations. Therefore, future research done should stress on amending its weaknesses besides extending the knowledge in this subject matter.